Metagenomics Reveals That Intravenous Injection of Beta-Hydroxybutyric Acid (BHBA) Disturbs the Nasopharynx Microflora and Increases the Risk of Respiratory Diseases - Qi, Jiancheng; Cai, Dongjie; Cui, Yaocheng; Tan, Tianyu; Zou, Huawei; Guo, Wei; Xie, Yue; Guo, Hongrui; Chen, Shi-Yi; Ma, Xiaoping; Gou, Liping; Cui, Hengmin; et al. (Frontiers in Microbiology, 2021)
It’s widely accepted that the maintenance of microbial diversity is essential for the health of the respiratory tract, but there are almost no researches on the correlation between starvation and respiratory tract microbial diversity. In the present study, saline/BHBA intravenous injection after dietary restriction was used to imitate different degrees of starvation. Total 13 healthy male yaks were imposed to different dietary restriction and intravenous injection, and their nasopharyngeal microbiota profiles were obtained by metagenomic shotgun sequencing. In healthy yaks, the top four dominant phyla were Proteobacteria (33.0%), Firmicutes (22.6%), Bacteroidetes (17.2%), and Actinobacteria (13.2%), and Clostridium botulinum (10.8%) was the most dominated species. It was found that nine days’ dietary restriction and two days’ BHBA injection (imitating severe starvation) significantly decreased the microbial diversity and disturbed its structure and functional composition, which indicated the higher risk of respiratory diseases. The study also implied that oral bacteria played an important role in the maintaining of nasopharynx microbial homeostasis. This study investigated the correlation between starvation and nasopharynx microbial diversity for the first time, and discussed the possible mechanism under this correlation, providing new ideas for the prevention of respiratory diseases.